CORRELATION BETWEEN DEPRESSION LEVELS AND HYPERTENSION INCIDENCE AT THE RESILIENT ELDERLY SCHOOL (SELANTANG) IN PASURUAN CITY, EAST JAVA - Nisya Aulia Aziza; Adi Sucipto; Desty Ervira Puspaningtyas; Thomas Aquino Erjinyuare Amigo; Dwi Endah Kurniasih; Puspita Mardika Sari (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Hypertension is a global health issue, particularly among the elderly, and can be influenced by psychological factors such as depression. This study investigated the relationship between depression and hypertension among the elderly in the SELANTANG community, Pasuruan City. Utilizing a cross-sectional design, the research involved 175 elderly participants from a total population of 240. Data were collected in August 2023 using the Geriatric Depression Scale (GDS) and blood pressure measurements. Results showed that most participants had isolated systolic hypertension, with an average systolic pressure of 142.58 mmHg and diastolic pressure of 83.00 mmHg. Despite a normal average depression score of 2, Spearman’s rank analysis indicated no significant correlation between depression levels and hypertension (p = 0.885 and p = 0.901). These findings suggest that hypertension management in the elderly should prioritize factors such as diet, lifestyle, and physical activity.